2023
DOI: 10.3390/electronics12071643
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Prediction Model for Listed Companies Based on CNN-LSTM and Attention Mechanism

Abstract: The financial market has been developing rapidly in recent years, and the issue of credit risk concerning listed companies has become increasingly prominent. Therefore, predicting the credit risk of listed companies is an urgent concern for banks, regulators and investors. The commonly used models are the Z-score, Logit (logistic regression model), the kernel-based virtual machine (KVM) and neural network models. However, the results achieved could be more satisfactory. This paper proposes a credit-risk-predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…At the same time, large and small values in the data will affect the robustness of the model, leading to a large error in the prediction effect compared to the actual. Therefore, a new model (called CNN-LSTM model) is built by combining the advantages of extracting CNN and LSTM, respectively, which makes full use of CNN's feature information extraction capability and LSTM's sensitivity to time series data [25][26][27][28], thus improving the prediction of carbon dioxide emissions.…”
Section: Construction Of a Carbon Dioxide Prediction Modelmentioning
confidence: 99%
“…At the same time, large and small values in the data will affect the robustness of the model, leading to a large error in the prediction effect compared to the actual. Therefore, a new model (called CNN-LSTM model) is built by combining the advantages of extracting CNN and LSTM, respectively, which makes full use of CNN's feature information extraction capability and LSTM's sensitivity to time series data [25][26][27][28], thus improving the prediction of carbon dioxide emissions.…”
Section: Construction Of a Carbon Dioxide Prediction Modelmentioning
confidence: 99%
“…For example, recent work in urban planning has shown that CNNs can be combined with LSTM models to predict particulate matter such as PM2.5 (very small particles in air with diameters less than or equal to 2.5 µm) in urban areas, as shown in the work of [28]. The fusion model can also be used to predict other things, such as credit risk prediction [29] and emotion monitoring [30]. All experimental results proved that the fusion model has the highest prediction accuracy.…”
Section: Related Workmentioning
confidence: 99%